(untitled) (Informatica, 2024)
The Lightweight On-demand Ad hoc Distance-vector Routing Protocol - Next Generation (LOADng) has played a pivotal role in shaping the landscape of the Internet of Things (IoT) and associated standards. It enables sophisticated communication among compact, intelligent, and embedded networking devices. LOADng focuses primarily on establishing secure connections between interconnected objects, ensuring reliable and protected communication. This study presents an innovative methodology that utilizes fuzzy logic to identify hello flood attacks directed at the LOADng routing protocol. The effectiveness of this proposed approach was evaluated using the Cooja simulator on the Contiki operating system, with the findings indicating that the fuzzy-based method successfully detects hello flood attacks on the LOADng protocol.